Enhancing Students’ Writing Quality in a Blended Learning Environment - Ni Putu Lila Sri Hari; I Dewa Gede Rat Dwiyana Putra; Putu Santi Oktarina (Unika Santu Paulus Ruteng, 2023)
This study aims to explore the best implementation of Blended Learning Model to enhance students’ writing quality. This is a Classroom Action Research where Blended Learning Model was applied using two different media. The mean score result show that students’ writing quality improve from 67.83 to 75.74 at the first cycle, where videos was applied in Blended Learning Model. At the second cycle where was video was switched to PowerPoint, the students’ writing quality reach the mean score of 83.10. These findings suggested that the application of PowerPoint in Blended Learning could address the students’ problem in term of word choice, generic structure, and grammar better than videos. Students also showed positive attitude, response, as well as active participation in learning. It shows that the application of PowerPoint in Blended Learning Model could maintain students’ attention that could give better result in learning writing. Therefore, the media selection in Blended Learning environment should consider its ability in maintaining students’ attention.